Islamic Worldview terhadap Integrasi Sains dan Agama - Mujahid, Kasori; Burhanuddin, Burhanuddin; Assalam, Gholib; Husnia, Siti (TSAQOFAH, 2025)
The concept of the Islamic worldview is essentially a perspective derived from Islamic teachings, encompassing an understanding of existence, reality, and the purpose of life. As a system of knowledge, this worldview cannot be separated from science; rather, it has a close relationship with scientific inquiry. This article aims to analyze the relationship between science and religion from the perspective of the Islamic worldview, identifying points of convergence and divergence, as well as exploring how both can complement each other in shaping our understanding of the universe and human life. Through a multidisciplinary approach, this article delves into the role of science in Islam and how religious principles influence the development of scientific knowledge. Overall, this article argues that science and religion within the Islamic worldview are not in conflict; instead, they can coexist in the pursuit of a greater truth.